135k views
0 votes
−3x + y = 4,

−9x + 5y = −1

1 Answer

1 vote

Explanation:

Option 1:

−3x + y = 4.........eq. 1

−9x + 5y = −1.....eq. 2

from eq. 1,

we get y = 4 +3x...................eq. 3

substitute eq. 3 into eq. 2.

-9x + 5(4 +3x) = -1

-9x + 20 + 15x = -1

-9x + 15x = -1 – 20

6x = -21

x = –3.5

to solve y, use the obtained x in eq. 3,

y = 4 + 3(–3.5)

y = -6.5

User Yashas
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.